Adsorptive Removal of Bisphenol A Using Zeolitic Imidazolate Framework (ZIF-8) - Mahmad, A. (Springer Science and Business Media B.V., 2021)
Bisphenol A is one of the compounds capable of causing endocrine disruption and is also a pollutant in the environment. Even in low concentrations, these pollutants have significant effects on humans, animals and the environment. This workâs main goal was to study the performance of adsorption of BPA using a Metal Organic Framework (MOF), ZIF-8. Textural analysis has shown the porous nature of the MOF as possessing surface areas of 1299Â m2/g. Other characterizations were conducted using Fourier Transformed Infrared (FTIR) spectroscopy, X-ray Photoelectron Spectroscopy (XPS), Field Emission Scanning Electron Microscope (FESEM), and powdered X-ray diffraction (XRD). The MOF was evaluated for application as an adsorbent for (BPA) removals in an aqueous solution. Adsorption isotherms using Langmuir and Freundlich models were investigated, while kinetics was studied using pseudo-first-order and pseudo-second-order. In conclusion, this MOF exhibited favorable features of ideal adsorbents for BPA removal in wastewater. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.